Some considerations on the subject of questioning, of Heidegger and Foucault, of the Cartesian epistemological perspective - Fernández Agis, Domingo (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The questioning of the epistemological perspective characteristic of the modernity, brings into question the Cartesian exclusion of the possibility that, in Foucault could be defined as a «reasonable Unreason». Although, in general, the thought of Derrida also points in the same direction, negative values of Foucault’s reading of the radical separation between Reason and Unreason in Descartes, just pretending to make a defense of some deep reading the Meditations that, in his view, would yield result in disqualification of the interpretation Foucault History of Madness. However, not only the replica of the latter in «My body, this paper, this fire» but, above all, the re-reading of the text of Descartes, come to support Foucauldian interpretation. This paper, after analyzing the Heideggerian roots of such approaches, performs a re-reading of Foucault, Derrida controversy known. My purpose is to show how, rereading the above controversy from certain budgets set by Heidegger, the result of it is illuminated in a new light.
Keywords: Heidegger; Foucault; Derrida; reason; madness; modernity